25‐Hydroxyvitamin D3 and its C‐3 epimer are elevated in the skin and serum of Skh‐1 mice supplemented with dietary vitamin D3. Issue 10 (20th July 2017) - Teegarden, Matthew D.; Campbell, Amanda R.; Cooperstone, Jessica L.; Tober, Kathleen L.; Schwartz, Steven J.; Oberyszyn, Tatiana M.
Abstract : Scope: UV exposure is a risk factor for keratinocyte carcinoma (KC) while critical for endogenous vitamin D production. We investigated dietary modulation of skin and serum 25‐hydroxyvitamin D3 (25OHD3 ) and its C‐3 epimer (C3epi) in a mouse model of KC. C3epi is an under‐investigated metabolite of vitamin D with respect to its biological implications. Methods and results: Male and female Skh‐1 mice were supplemented with 25, 150 or 1000 IU/kg diet vitamin D3 for 25 weeks, with some exposed to UV light. Skin and serum vitamin D metabolites were quantitated using HPLC‐MS/MS ( n = 3 per dose/sex/UV treatment). Serum and skin 25OHD3 and C3epi significantly increased with dose ( P <0.0001), but with different response patterns. UV exposure significantly attenuated serum, but not skin, levels of both metabolites ( P <0.001, P = 0.0287), while up‐regulating expression of renal Cyp24a1 ( P < 0.01). A dose by sex interaction trended toward significance with serum and skin levels of C3epi, wherein male mice attained higher levels of C3epi with higher dietary vitamin D3 . This reflected a similar, but non‐significant pattern in average tumor size. Conclusion: The complex relationship between vitamin D and KC requires further investigation. This study provides insight into modulation of local and systemic vitamin D status with dietary supplementation. Abstract : Male and female mice are fed increasing doses of vitamin D3 . A subset of mice is exposed to UV light. Levels of 25OHD3 and its under‐researched C‐3 epimer form are elevated in both serum and skin. Metabolite levels in serum, but not skin, are affected by UV exposure, and a trending effect of sex on C3‐epi levels is detected.